PEMAHAMAN JEMAAT TENTANG KARUNIA-KARUNIA ROH KUDUS BERDASARKAN 1 KORINTUS 12:7-11 - Wandi Orlando Siahaan; Gregorius Suwito; Gidion Gidion (JOURNAL of THEOLOGICAL STUDENTS, 2022)
Ignorance of the gifts of the Holy Spirit can be the cause of the backward growth of the Church. Researh was conducted to find out how the congregation's understanding of the gifts of the Holy Spirit is based on 1 Corinthians 12:7-11 in Beth-El Tabernacle Christ Alpha Omega church, Temanggung. This research is a qualitative research with one variable. From these questions, the results of this study indicate that 79% of the congregation have understood. Then the other 21% of the congregation do not understand all the gifts of the Holy Spirit which are written in 1 Cor 12:7-11.